Nutritional Value of Gastropod Cassidula from the Mangrove Area of Desa Bakau, Sambas Regency, West Kalimantan - Oktavia; Warsidah; Ikha Safitri; Mega Sari Juane Sofiana; Apriansyah; Yusuf Arief Nurrahman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Desa Bakau is located in Sambas Regency, West Kalimantan which has the potential for mangrove forests with an area of ± 305 Ha. Ecologically, mangrove forests have various roles, one of them is as a habitat for various types of aquatic biota, including gastropods. Several gastropods have important economic value for the community as food and medicine. The local community catches and consumes the mangrove gastropods. As a food ingredient, gastropods have a high nutritional content and essential macro minerals. Gastropods can be used as an alternative source of animal protein at an affordable price. This study aimed to determine the nutritional value of the gastropod Cassidula from the mangrove area of Desa Bakau, Sambas Regency, West Kalimantan. Quantitatively, nutrient content such as protein, carbohydrates, fat, moisture, and ash content were determined according to the AOAC (2005) standard method, whereas macro minerals content (Na, K, Mg, Ca, and P) was carried out according to the AOAC method (2016) using Atomic Absorption Spectroscopy (AAS). The result showed that Cassidula had a protein content (57.02%) with the highest value compared to other types of nutrients. In addition, Cassidula also contained an essential macro mineral, such as calcium (37.0006 mg/kg) with the highest value followed by sodium (21.7364 mg/kg), respectively. The results showed that Cassidula can be used as an alternative food ingredient for human.